Influencia del ciberperiodismo en los habitantes de la Parroquia Los Guayacanes sector San Jorge año 2022 - Cuji Rizo, Ingrid Janina (2022)
Digital journalism or as it is currently known cyberjournalism is a means of direct and accessible information for readers who are interested in events in the world. Through digital journalism, information can be obtained at the moment the event unfolds, in addition, this medium offers the possibility that each of the people can exchange their opinions about the news as well as contribute with a relevant investigation. Unlike the others, this medium contains several advantages, such as providing news in real time, with sound, images, links to other pages, and interaction with society. Cyberjournalism involves the entire journalism process, taking advantage of the resources offered by technology, promoting the constant development of information that the audience can receive at any time and place. The different social networks allow us to maintain immediate communication with your followers, it also offers us the possibility of talking, listening and communicating directly with your community, it is a more human service. It should be noted that it is a powerful means of disseminating news that also allows us to capture the attention of users or customers and in turn we can listen to the audience and communicate more directly. Due to the characteristics of this research work, the type of descriptive and explanatory research was used. In this project, data collection instruments were used, such as survey questions applied to a group of people from the Los Guayacanes parish, "San Jorge" sector, Quevedo canton. The survey was carried out on 170 people from the Los Guayacanes parish, “San Jorge” sector. Therefore, the conclusion was reached that the main purpose of journalism is to provide citizens with accurate and timely information to assert their rights before society. Not all the news that is disseminated through social networks is true, many times altered content is uploaded to attract people's attention; That is why we must be critical and keep ourselves informed through reliable digital media. It is recommended to design a training plan with communication strategies in this way, the citizen and reader has the possibility to give their opinion and participate in the debate, an action that is increasingly common in the multimedia platforms of newspapers, radio stations and TV channels. with an online presence.